Formulating Community Empowerment Strategies for the Tourism Destination Program in Banyurejo Village, Sleman District, The Special Region of Yogyakarta - Agustina , Clara Riska; Nugroho, Hanantyo Sri (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This paper explores strategies for community empowerment within the tourist destination program in Banyurejo Village, Sleman Regency, specifically focusing on Si Cangkring Valley Tourism Village as a form of community empowerment. Employing a qualitative descriptive method, the research utilizes analysis to formulate and evaluate strategies aimed at leveraging strengths and opportunities, while mitigating weaknesses to address emerging threats. The second phase employs the Litmus Test tool to prioritize strategic issues, assessing each issue through 13 specific questions to guide strategy formulation and evaluation. The findings highlight strengths and weaknesses from the internal environment, alongside opportunities and threats from the external environment identified in the strategic environmental analysis. This process identifies four key issues, leading to a strategic evaluation that prioritizes budget utilization and the strength of supporting information media to enhance community engagement in tourist villages, maximizing strategic value. Subsequently, these issues are formulated into a cohesive strategic program.